PENGARUH KOMPETENSI PROFESIONAL PENDIDIK DALAM MENGEMBANGKAN KARAKTER SISWA (Implementasi Kurikulum Merdeka di MIN 1 Sumenep) - Maulidina, Nadila; Karimah, Anisatul (JEMI, 2024)
This research aims to determine the potential of professional teachers in the independent curriculum to develop the character of MI Negeri 1 Sumenep students. The method used in this writing is the descriptive-qualitative research method, which is a research method by observing, analyzing, observing, interviewing and describing an event or phenomenon that occurs in a research object. So professional teachers form character so that students have potential in their personalities. Applying the character formed by professional teachers is very beneficial.